Incentive provision to farm workers in post-socialist settings: evidence from East Germany and North Kazakhstan - Martin Petrick (International Food and Agribusiness Management Review, 2017)
This article explores the current practice of motivating agricultural workers in post-socialist settings. In addition, it attempts to evaluate the different wage systems observed in reality and better understand under which conditions they are reformed. It does so by contrasting the experience of two extreme cases representing fast and slow reform advance, East Germany and North Kazakhstan. The primary data for the analysis comes from cross-sectional farm surveys conducted by various researchers in both countries. East German farmers quickly replaced the inherited Soviet-style piece rate payment system by simple time rate schemes, augmented by wage premia for certain performance parameters, especially in livestock. To the contrary, the piece rate approach persists in many farms in North Kazakhstan. Moreover, the latter rarely use non-wage incentives to motivate their workers. In Kazakhstan, farms using either mixed systems or pure piece rates were more productive than the reference group using pure time rates. Labour cost per worker were lowest for pure time rate systems in both countries, followed by mixed bonus systems, whereas pure piece rate systems implied the highest cost in Kazakhstan. Kazakhstani managers tend to move away from the Soviet piece rate system if external investors become engaged in farming operations.
Keywords: M52; P32; Q12; 330; human resource management; labour supervision; performance pay; post-Soviet agriculture; agroholdings